2000
DOI: 10.1046/j.1365-2257.2000.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma and immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is frequently encountered in patients with lymphoproliferative disorders. However this is only rarely reported in patients with multiple myeloma. We describe three cases who presented initially with the clinical manifestations of ITP but were subsequently found to have multiple myeloma. Platelet count increments to standard treatment modalities for ITP were observed in all three patients with transient or partial response. The importance of recognizing the immune mediated thromboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…To date, 7 cases of ITP associated with MM have been reported in the literature (Table 1) [1][2][3][4] (comprised of 5 men and 2 women). Five of the patients were young (36-55 years old), and two patients were 67-year-old.…”
Section: Discussionmentioning
confidence: 98%
“…To date, 7 cases of ITP associated with MM have been reported in the literature (Table 1) [1][2][3][4] (comprised of 5 men and 2 women). Five of the patients were young (36-55 years old), and two patients were 67-year-old.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Aryal et al [5] reported the first case of a patient with multiple myeloma who developed AIN, in which the T cell receptor c chain gene rearrangement indicated the presence of a clonal T cell proliferation, suggesting the possible existence of a relationship between monoclonal B cell and T cell lineages, and AIN. In addition, there have been only rare reports of ITP developing in patients with multiple myeloma [7]. The monoclonal protein itself might lead to AIN and ITP, although it could not be undetected in the serum or urine in our patient.…”
Section: Discussionmentioning
confidence: 58%
“…It may occur in association with various diseases, including systemic lupus erythematosus (SLE) and human immunodeficiency virus (HIV) infection, or as a primary or idiopathic condition in the absence of any underlying disease. A few cases of ITP associated with multiple myeloma have also been reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…, very few cases of autoimmune disorders related to multiple myeloma (11,12) and only one case complicated with hyperthyroidism after ASCT for multiple myeloma have been reported (7). (8,9,14) i g u r e 1 .…”
Section: Recently Autologous Stem Cell Transplantation (Asct) Has Bementioning
confidence: 99%
“…1) (6,16 (3). Autoimmune thrombocytopenia has only rarely been associated with multiple myeloma itself (11,12). Evans syndrome appears to be a more aggressive and a potentially life-threatening condition than either ITP or AIHA alone (13), and thus, its treatment is sometimes difficult.…”
Section: Recently Autologous Stem Cell Transplantation (Asct) Has Bementioning
confidence: 99%